Supervisory fuzzy learning control for underwater target tracking - Kia, Chua; Arshad, Mohd Rizal; Adom, Abd Hamid; Wilson, Philip A. (World Academy of Science, Engineering and Technology, 2009)
Link to publisher's homepage at http://www.waset.org/journals